TERMS DICTIONARY COMPUTER APPLICATIONS USING MICROSOFT VISUAL BASIC 6.0 - Eva Adriana Yublina Derewila; Yuce Yuliani , SKom, MMSI (Jurnal Sistem Informasi, 2007)
Currently the use of computers in various fields has become a necessity, because computers have several advantages, including the amount of which can save a lot of data, computers can also help us to give us the information we need quickly, so the job will be easier. In scientific writing, the writer makes Computer Applications Dictionary term with the goal of keeping people - people who do not know the term computer can find out in a more practical but still got the sense that weight. Hopefully with this application is expected to help the society who want to know more about computers, especially about the terms that have anything to do with computers. In Scientific Writing this makes the author using word processing software Microsoft Word 2003 because this software easy to use and already famous as a good word processor. Whereas in making the program the author uses the Microsoft Visual Basic 6.0 software because this software is not too difficult to understand, while also able to manage data properly.